Minimalism. - The Tate Gallery, London (Liverpool : The Tate Gallery, 1989)
Andre, Carl ; Flavin, Dan ; Judd, Donald ; Lewitt, Sol ; Serra, Richard
Minimalism, the collection display, The Tate Gallery, Liverpool, 21 March 1989 - 18 February 1990
boek